(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The integration of satellite communication with 5G networks presents a promising avenue to extend the coverage and capacity of next-generation mobile communication systems. This article outlines the key aspects and challenges of integrating satellite communication with 5G networks. Satellite communication offers wide-area coverage and global reach, making it an attractive solution for providing connectivity in remote or underserved areas where terrestrial infrastructure is limited. By integrating satellite communication with 5G networks, it is possible to enhance the connectivity experience for users, enable seamless handover between satellite and terrestrial networks, and support a wide range of applications and services.